Impact of Presence, Level, and Closure of a Stoma on Growth in Young Children: A Retrospective Cohort Study - Eeftinck Schattenkerk, Laurens Donald; Vogel, Irene; de Jong, Justin R.; Tanis, Pieter J.; Gorter, Ramon; Tabbers, Merit; van Heurn, L. W. Ernest; Musters, Gijsbert; Derikx, Joep P. M. (European Journal of Pediatric Surgery, 2023)
Introduction A stoma will cause nutrients loss which could result in impaired growth. Impaired growth can negatively impact long-term development. This study aims to evaluate: (1) the effect of stomas on growth comparing small bowel stoma versus colostomy and (2) if early closure (within 6 weeks), proximal small bowel stoma (within 50 cm of Treitz), major small bowel resection (≥ 30 cm), or adequate sodium supplementation (urinary level ≤ 30 mmol/L) influences growth.Methods Young children (≤ 3 years) treated with stomas between 1998 and 2018 were retrospectively identified. Growth was measured with weight-for-age Z-scores. Malnourishment was defined using the World Health Organization's definition. Comparison between changes in Z-scores at creation, closure, and a year following closure was done by Friedman's test with post hoc Wilcoxon's signed rank test or Wilcoxon's rank-sum test when necessary.Results In the presence of a stoma in 172 children, 61% showed growth decline. Severe malnourishment was seen at the time of stoma closure in 51% of the patients treated by small bowel stoma and 16% of those treated by colostomy. Within a year following stoma closure, 67% showed a positive growth trend. Having a proximal small bowel stoma and undergoing major small bowel resection led to significantly lower Z-scores at closure. Adequate sodium supplementation and early closure did not lead to significant changes in Z-scores.Conclusion Stomas have a negative impact on growth in the majority of children. This impact might be decreased by preventing small bowel stomas when possible, specifically proximal stomas, and limiting small bowel resection. Since stoma closure is essential in reversing the negative effect on growth, we opt that early closure might result in an early shift to catch-up growth.
Keywords: surgery; stoma; sodium; supplementation; growth